Anterior cervical discectomy and fusion without plate (ACDFWP) versus anterior cervical disc arthroplasty (ACDA) for cervical spondylosis: A meta-analysis and literature review - Li, Sihan; Song, Hongmei; Peng, Jiajie; Zheng, Rong; Li, Pengfei; Lin, Xiangying; Zhong, Degui; Huang, Minghan; Asakawa, Tetsuya (Intractable & Rare Diseases Research, 2022)
This meta-analysis compared the clinical outcomes between two alternative surgeries for patients with cervical spondylosis, namely anterior cervical discectomy and fusion (ACDF) without plate (ACDFWP) vs. anterior cervical disc arthroplasty (ACDA). We searched databases, including PubMed, EMBASE, Cochrane Library, Google Scholar, and Web of Science (firstly available-2019). A standard meta-analysis was performed with the included studies. A Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool was used for the evaluation of the study quality of nonrandomized-controlled trials (nRCTs), while a Risk of Bias (RoB) battery was used for randomized controlled trials (RCTs). Eight studies involving 640 patients were included. No significant difference was found in the indices of Neck Disability Index (NDI) score, Visual Analog Score (VAS), Japanese Orthopaedic Association (JOA) score, operative time, blood loss, Swallowing Quality of Life Score (SWAL-QL), and complications. Cervical alignment was significantly better in the ACDFWP than in ACDA (mean difference (MD) = −0.67, 95% confidence interval (CI) [−1.11, −0.23], P = 0.003, I2 = 20%). Although the alternative ACDFWP was slightly superior in terms of the index of cervical alignment, the limited research on this subject present insufficient evidence. Further well-designed studies are warranted in the future.